2021
DOI: 10.3389/fpsyg.2021.667041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small-Sided Game Interventions on the Technical Execution and Tactical Behaviors of Young and Youth Team Sports Players: A Systematic Review and Meta-Analysis

Abstract: Background: Small-sided games (SSGs) are an adjusted form of official games that are often used in training scenarios to introduce a specific tactical issue to team sports players. Besides the acute effects of SSGs on players' performance, it is expectable that the consistent use of these drill-based games induces adaptations in the technical execution and tactical behaviors of youth team sports players.Objective: This systematic review with meta-analysis was conducted to assess the effects of SSG programs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 53 publications
3
26
0
4
Order By: Relevance
“…One issues with SSGs is that it does provide some intra- and inter-individual variability in high-intensity locomotor demands and possibly some under-stimulation of high-intensity running and sprinting ( Clemente, 2020 ). However, SSGs provide an adequate stimulus for improving aerobic fitness ( Moran et al, 2019 ) while facilitating technical/tactical stimuli ( Clemente & Sarmento, 2020 ; Clemente et al, 2020 , 2021c ). A recent meta-analysis comparing SSGs with conventional endurance training, reported similar effects for positive aerobic fitness development ( Moran et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One issues with SSGs is that it does provide some intra- and inter-individual variability in high-intensity locomotor demands and possibly some under-stimulation of high-intensity running and sprinting ( Clemente, 2020 ). However, SSGs provide an adequate stimulus for improving aerobic fitness ( Moran et al, 2019 ) while facilitating technical/tactical stimuli ( Clemente & Sarmento, 2020 ; Clemente et al, 2020 , 2021c ). A recent meta-analysis comparing SSGs with conventional endurance training, reported similar effects for positive aerobic fitness development ( Moran et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most intervention studies are based on models with few sessions (as observed in the inconclusive results with less than 12 intervention sessions). 6,7 Despite the study by Clemente et al 8 showing evidence of improvement in technical execution after <17 and >17 (in most studies, training session interventions varied from 18 to 24 sessions) small-sided games training sessions, the authors describe that short training program may not be enough to favor the development of technical skills in elite youth players.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to measure exercise intensity in SSGs through player movement, and the physiological responses and perception of effort [18]. The coach controls a set of variables that influence exercise intensity in SSGs [19], such as field area, the number of players, coach feedback, training planning (continuous or interval and rest-time manipulation), modification of the rules, and the use of goals and goalkeepers (GK) [9,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%